The Impact of Strategy Implementation on the Performance of Ugandan State Agencies: A Quantitative Study - Nuwagaba, Arthur; Angima, Caren; Kisekka Namateefu , Lydia; Mugizi, Tom (Journal of Economics and Behavioral Studies, 2023)
This study examines how strategy implementation affects Ugandan state agencies’ performance. It conceptualizes strategy implementation as operationalization and institutionalization, and measures performance by efficiency and effectiveness. This study surveyed 160 state agencies using a cross-sectional design and a structured questionnaire. The top management team (TMT) members of each agency, including CEO/Managing Director, Deputy/Assistant CEO, Corporation Secretary, and Heads of Department, were the respondents. At least three TMT members from each agency participated in the online survey, which was chosen due to the COVID-19 restrictions. The data analysis methods were factor analysis, descriptive, and multilinear regression analysis. The study adhered to the ethical principles of informed consent, confidentiality, and anonymity. Ugandan state agencies perform better when they implement their strategies effectively. The statistical analysis reveals that institutionalization is a key driver of performance outcomes, with a positive and highly significant coefficient (p < 0.000). On the other hand, operationalization has a positive but insignificant coefficient (p = 0.140), indicating a weak link between operationalization and performance. These findings highlight the importance of aligning the strategy with the organization’s internal environment. The study provides invaluable contribution the realm of strategic management, particularly within the public sector, focusing primarily on the performance of state agencies in Uganda. It is groundbreaking research that explores this relationship in a developing country. It methodically examines the profound effect that the execution of various strategies has on these entities. This study contributes to the strategic management literature in the public domain. The insights and recommendations derived from this study are valuable for professionals and policymakers involved in creating and implementing strategic plans within the public sector. This study offers practical and theoretical contributions for strategy implementation and performance in public sector contexts. It suggests that state agency managers and policymakers should foster a supportive culture, enhance leadership skills, facilitate communication channels, allocate adequate resources, and adapt to environmental changes to improve strategy execution and outcomes. It also adds to the literature on strategic management in public sector contexts, especially in developing countries.